PENGEMBANGAN MODUL BIOLOGI BERBASIS GUIDED DISCOVERY LEARNING BAGI SISWA SMP - Intan Nuraini Harahap; Nursamsu Nursamsu; Setyoko Setyoko (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
In today's educational development, teachers are expected to be creative thinkers and producers of a variety of learning media. An additional type of educational resource that can be employed is a module. The purpose of the study is to assess whether a course on biology using guided discovery will be viable and useful. R&D is a methodology with materials and response language for JHS students, as well as validation tools from media experts. An average of 85 per cent of data collected through the validation process by qualified experts was found to meet very good criteria; similar levels were 80% for media and 95% for language experts. With extremely realistic criteria, the average score for teachers' and students' responses in the practical test was 88% and 90%, respectively. Based on the findings of this research, a biology course based on guided discovery learning can be used as teaching material for contaminated materials.